Embedded UHF RFID tag design process for rubber transmission belt using 3D model - Kanwar, Kelash; Mager, Thomas; Hilleringmann, Ulrich; Geneiss, Volker; Hedayat, Christian (2014 IEEE RFID Technology and Applications Conference (RFID-TA))

Modeling and characterization of CP-PLL phase noise in presence of dead zone - Hangmann, Christian; Wullner, Ingo; Hedayat, Christian; Hilleringmann, Ulrich (2014 IEEE 12th International New Circuits and Systems Conference (NEWCAS))

Titanium disilicide as hot side metallization layer for thermoelectric generators - Hilleringmann, Ulrich; Schonhoff, M.; Assion, F. (2013 Africon)

Händel-Solisten: Repertoire und Reisen – Betrachtungen an ausgewählten Beispielen - Höink, Dominik (Aufführungen von Händels Oratorien im deutschsprachigen Raum (1800-1900). Bibliographie der Berichterstattung in ausgewählten Musikzeitschriften)

„Der Vielgereiste ... hielt Vaterlandsliebe und -treue allzeit hoch in Ehren“. Der ,deutsche‘ Händel im Kaiserreich und in der Weimarer Republik - Höink, Dominik (Händel-Jahrbuch)

Aufführungen von Händels Oratorien im deutschsprachigen Raum (1800-1900). Bibliographie der Berichterstattung in ausgewählten Musikzeitschriften

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Marie-Luise (onlinejournal kultur & geschlecht)

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Mary (onlinejournal kultur & geschlecht)
Die Politiken bebilderter Berichterstattung und die Temporalität unserer gegenwärtigen Aufmerksamkeitsökonomie betrachtend, wird den Fragen nachgegangen, wieso die Reaktionen auf die NSA-Affäre so oft von Zynismus oder Resignation gekennzeichnet sind oder sogar ganz ausbleiben, und wer eigentlich betroffen ist und reagieren sollte. Die Überlegungen sind der Versuch, die NSA-Affäre im Spannungsfeld von Technikverliebtheit und Blackboxing, den Bedingungen von Medienereignissen und Geheimdienstpraktiken, der Krise des Journalismus sowie unseren Gewohnheiten im Umgang mit der uns umgebenden rechnenden Umwelt zu situieren.

Subjektivierung als Artikulation diskursiver Ordnungen. Zur Aneignung von Subjektpositionen im Kontext der Entwicklung automatisierter Videoüberwachung - Hälterlein, Jens; Möllers , Norma; Spies, Tina (Zeitschrift für Diskursforschung)